Longitudinally extensive transvers myelitis: a single instution experience - Yilmaz, E.; Tuncer, M. A.; Khasiyev, F.; Gumeler, E.; Ilica, A. T.; Gocmen, R.; Karabudak, R. (Sage Publications Ltd, 2018)
[Abstract Not Available]
34th Congress of the European-Committee-for-Treatment-and-Research-in-Multiple-Sclerosis (ECTRIMS) -- OCT 10-12, 2018 -- Berlin, GERMANY